Achieving the Green Building Council of Australia's World Leadership Rating in an Office Building in Perth - Love, Peter; Niedzweicki, M.; Bullen, Peter; Edwards, D. (University of Johannesburg, 2012)
The issues influencing the construction of Western Australia’s first six-star Green Star energy-rated commercial office building are examined. Green Star is a comprehensive, national, voluntary environmental rating system that evaluates the environmental design and construction of buildings and is undertaken by the Green Building Council of Australia. A six-star rating signifies “world leadership” in environmentally sustainable design and construction. The case study presented in this paper describes how a client acted as a catalyst for driving the sustainability agenda. The client’s key drivers for implementing sustainable technologies were procurement and organizational resources. Existing building regulations and a lack of government incentives were identified as being the main barriers to implementing sustainable technologies. The case findings presented provide an opportunity for clients and practitioners to learn from the experiences of others who have, and continue to address the environmental challenges facing the built environment.